Characterization of flavor profile of beef jerky from different regions of China using gas chromatography–mass spectrometry, electronic tongue, and electronic nose - Bayierta Bayinbate; Linwei Yang; Iftikhar Hussain Badar; Yue Liu; Lang Zhang; Yingying Hu; Baocai Xu (Food Chemistry: X)
This research utilized gas chromatography–mass spectrometry (GC–MS), electronic tongue (E-tongue), electronic nose (E-nose), and sensory analysis to investigate the flavor profiles of beef jerky from four specific regions of China: Xinjiang, Tibet, Sichuan, and Inner Mongolia. Physical analysis revealed that beef jerky from Inner Mongolia had lower moisture content and water activity, while Tibet and Inner Mongolia samples exhibited lower pH values. Seventy-two volatile compounds were identified and quantified among all samples, indicating significant regional variations in aldehydes, alcohols, and esters. Heatmap cluster analysis clearly explained the unique regional flavor profiles. Furthermore, partial least squares regression analysis using E-nose and E-tongue showed significant correlations with the volatile compounds and sensory attributes. These findings indicate the efficacy of a multi-faceted analytical approach for flavor differentiation and emphasize the need for further research to understand the mechanisms behind developing characteristic flavors in beef jerky.